The Pathology of Orthopedic Implant Failure Is Mediated by Innate Immune System Cytokines - Stefan Landgraeber; Marcus Jäger; Joshua J. Jacobs; Nadim James Hallab (Mediators of Inflammation)
All of the over 1 million total joint replacements implanted in the US each year are expected to eventually fail after 15–25 years of use, due to slow progressive subtle inflammation at the bone implant interface. This inflammatory disease state is caused by implant debris acting, primarily, on innate immune cells, that is, macrophages. This slow progressive pathological bone loss or “aseptic loosening” is a potentially life-threatening condition due to the serious complications in older people (>75 yrs) of total joint replacement revision surgery. In some people implant debris (particles and ions from metals) can influence the adaptive immune system as well, giving rise to the concept of metal sensitivity. However, a consensus of studies agrees that the dominant form of this response is due to innate reactivity by macrophages to implant debris where both danger (DAMP) and pathogen (PAMP) signalling elicit cytokine-based inflammatory responses. This paper discusses implant debris induced release of the cytokines and chemokines due to activation of the innate (and the adaptive) immune system and the subsequent formation of osteolysis. Different mechanisms of implant-debris reactivity related to the innate immune system are detailed, for example, danger signalling (e.g., IL-1β, IL-18, IL-33, etc.), toll-like receptor activation (e.g., IL-6, TNF-α, etc.), apoptosis (e.g., caspases 3–9), bone catabolism (e.g., TRAP5b), and hypoxia responses (Hif1-α). Cytokine-based clinical and basic science studies are in progress to provide diagnosis and therapeutic intervention strategies.